Estimating the lifetime cost of childhood obesity in Germany: results of a Markov Model - Sonntag, Diana (Pediatric obesity, 2015)
Background: Child obesity is a growing public health concern. Excess weight in childhood is known to be associated with a high risk of obesity and obesity-related comorbidities in adulthood. Objectives: This study quantifies lifetime excess costs of overweight and obese adults in Germany taking the history of obesity in childhood into account. Methods: A two-stage Markov cohort state transition model was developed. At stage 1, the distribution of body mass index (BMI) categories was tracked from childhood (ages 3-17) to adulthood (age 17 and up). Based on these results, it was distinguished whether adults had been normal in weight or overweight/obese as child. At stage 2, age-specific and lifetime costs from age 18 onwards were simulated in two further Markov cohort models, one for each of the two BMI groups. Model parameter values were obtained from the German Interview and Examination Survey for Children and Adolescents (KiGGS), the German Microcensus 2009 and published literature. Results: When compared with normal weight adults, lifetime excess costs are higher among adults who had been overweight or obese at any point during childhood. For 18-year-old women (men), who have been overweight/obese during their childhood (ages 3-17), undiscounted lifetime excess costs are estimated at €19 479 (€14 524), with 60% (67%) occurring beyond age 60. Discounted (3%) lifetime excess costs are considerably lower, amounting to €4262 for men and €7028 for women. Conclusions: Because childhood obesity determines healthcare costs occurring in adulthood, interventions preventing the persistence of child obesity and obesity-related comorbidities during adulthood could have a substantial impact on reducing the burden of the obesity epidemic.